Jesus, jubilee, and the politics of God's reign - Collins Winn, Christian T. (Grand Rapids, MI. W.B. Eerdmans Publishing Company, 2023)
"Through examination of biblical text, this book offers a constructive theological elaboration of the claim that Jesus-in his life, death, and resurrection-is Gods kingdom in the flesh, which is now poured out through the power of the Spirit to empower and encourage communities and movements that long for liberation and life"--
Includes bibliographical references (pages 209-226) and indexes.
Keywords: Jesus Christ -- Kingdom